Compliance with regional courts judgments in SADC in the context of regional integration in Africa - Madala, Sithembele (Department of Commercial Law, 2025)
Existing research on the Southern African Development Community (SADC) Tribunal focuses mainly on how it has interpreted its human rights jurisdiction. Extant research on the SADC occasionally notes that Zimbabwe has not complied with all the SADC Tribunal judgments issued against it, but without any detailed analysis of the actual role of the tribunal and the contributions of its decisions to human rights protection and the rule of law. Consequently, based on non- compliance with tribunal decisions by Zimbabwe, some scholars have erroneously concluded that the tribunal is ineffective. The proponents of this view theorise that the SADC Tribunal can only be effective if its judgments are complied with or if a strong enforcement system supports its judgments. Contrary to these claims, however, a growing body of literature on international adjudication shows that international courts (ICs) are important beyond measures of state compliance. Furthermore, like many ICs, the SADC Tribunal depends on the member states and SADC Summit for enforcement and compliance with its judgments. The SADC Tribunal constitutive instruments make it difficult to enforce SADC Tribunal. Another structural problem that is the fact that even when ICs interpret a coherent set of treaties, unlike a national legislator that can go back and amend the law and override the court's interpretation, it is more cumbersome or even impossible to amend the treaty that the IC interpreted especially if enough number of the parties like the court's interpretation. This is structural. Moreover, the court had a slow institutional setup which suggests that it was never intended to function as a supranational court but to act as an advisory organ to the SADC by giving advisory opinions on contentious disputes. This also explains why the SADC Summit is the final arbiter and principal organ with the power to enforce tribunal judgments against recalcitrant state. The other structural problem facing an international court such as the SADC Tribunal is that even if interpret coherent set of treaties, it cannot amend domestic laws or override domestic courts interpretation since SADC Treaty and Tribunal Protocol does not create supranational legal system and supranational courts such as the European Court of Justice (ECJ) which has the power to override domestic laws and domestic court judgments that violate fundamental European Union (EU) laws. Therefore, the challenge with enforcement of tribunal judgments is structural and cannot be blamed on the tribunal. This thesis aims to evaluate the benefits and legal value of the SADC Tribunal beyond state compliance measures. It identifies and evaluates the multiple roles and functions of the tribunal, examines how it has performed these roles and assesses whether it has achieved its goals. This by no means suggests that compliance with the SADC Tribunal judgments is not essential. Rather, the thesis demonstrates that compliance is of limited use in explaining the tribunal's utility and importance. The research adopts goal-based and institutional design approaches to measure the utility of the SADC Tribunal by focusing on the institutional design of ICs and the multiple roles they perform to measure their institutional effectiveness. Drawing heavily on these approaches, the thesis concludes that the SADC Tribunal has performed its roles successfully owing to its institutional design, ratione materiae (subject matter jurisdiction) and jurisdiction ratione personae (personal jurisdiction). As an institution, the SADC Tribunal has achieved its intermediate goals of treaty interpretation and settlement of disputes. Beyond the intermediate goals set up by the SADC Tribunal's creators, this thesis showed the tribunal had achieved its ultimate goals of promoting human rights jurisprudence and developing SADC legal norms. Therefore, the SADC Tribunal has proven itself as an effective judicial institution that is ready to settle disputes between disputing parties. The prospects and potential of the SADC Tribunal should serve as a continuous incentive for reinstatement to its initial jurisdiction. These findings require some qualification, namely, as shown later in this research, that this does not mean that the SADC Tribunal decisions had significant impact at the domestic level. Rather, the evidence from this study indicates that the tribunal decisions had only marginal impact at the domestic level. This suggests that more effort must be made to mobilise civil society — including lawyers, human rights activists and domestic judges — to support the work of the SADC Tribunal. The evidence from this study intimates that it is through the efforts of such actors that tribunal judgments can have transformative impact in domestic courts.